1979
DOI: 10.1152/ajprenal.1979.237.3.f241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting on tubular phosphorus reabsorption

Abstract: In the thyroparathyroidectomized (TPTX) rat, fasting increased urinary phosphorus excretion by decreasing the tubular reabsorption of P1 (TRP) and resulted in hypophosphatemia. The administration of either sucrose or NaHCO3 prevented the metabolic acidosis associated with fasting and decreased the phosphaturia, indicating that the phosphaturia in fasting is in part due to metabolic acidosis. In rats on partial reduction of P1 intake selectively, the phosphaturic response to parathyroid hormone (PTH) was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In tubules isolated from LPD rats, the GNG rate was found to be decreased (49). It is tempting to speculate that lack of a response to PTH (or to DBcAMP) in animals fed LPD (7,8) may be due to suppressed GNG (49), and consequently to insufficient generation of cytoplasmic NAD+ needed to inhibit BBM uptake to Pi, in spite of an adequate supply of intracellular or extracellular cAMP. Such an explanation seems to be in agreement with our recent finding (39) which showed that infusion of PTH to rats maintained on NPD caused both phosphaturia and an increase in NAD+/NADH ratio, whereas in rats on LPD, both UpiV and NAD+/NADH ratio failed to increase in the response to PTH (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tubules isolated from LPD rats, the GNG rate was found to be decreased (49). It is tempting to speculate that lack of a response to PTH (or to DBcAMP) in animals fed LPD (7,8) may be due to suppressed GNG (49), and consequently to insufficient generation of cytoplasmic NAD+ needed to inhibit BBM uptake to Pi, in spite of an adequate supply of intracellular or extracellular cAMP. Such an explanation seems to be in agreement with our recent finding (39) which showed that infusion of PTH to rats maintained on NPD caused both phosphaturia and an increase in NAD+/NADH ratio, whereas in rats on LPD, both UpiV and NAD+/NADH ratio failed to increase in the response to PTH (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, cAMP added directly to the BBM vesicles in vivo had no effect on the BBM uptake of Pi (1, Kempson and Dousa, unpublished observations). Prominent changes in the rate of BBM uptake of Pi caused by variation of the dietary Pi intake (1,2) or by starvation (5), seem to occur independently of the regulatory influence of cAMP (1,6,7). Thus, although cAMP may indeed play a role in the actions of some phosphaturic hormones (e.g., PTH, calcitonin) (8), the intracellular factors which regulate the rate of Pi transport across BBM of proximal tubules in response to various pathophysiologic states remain to be identified (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has become apparent as a result of several phy siological studies that starvation has an effect on calcium metabolism \ Kcilu and Foster, 1976;Ascii, 1978;Beck et al, 1979;Pak and Galosy, 1979;Shires et al, 1980;Asch and Ascii, 1981]. However, there is no study on the effects of starvation on the ultrastructure of the pa rathyroid gland related to calcium and phosphorus metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological studies have shown that starvation had an effect on calcium metabolism (Kalu and Foster, 1976;Asch, 1978;Beck et al, 1979;Pak and Galosy, 1979;Shires et al, 1980;Asch and Asch, 1981). Recent morphological reports have suggested the changes of the parathyroid glands in starved mice (Isono et al , 1985) and starved golden hamsters .…”
Section: Starvationmentioning
confidence: 99%